Strategies and measures for implementing eco-labelling schemes in Singapore's construction industry - Low, S.; Gao, Patrick; See, Y. (Emerald Group Publishing Limited, 2014)
The issue of sustainability in the construction industry is very prominent, as the industry often causes adverse impacts on the environment through its use of large amounts of natural resources and by clearing large areas of their natural habitats. After the 1992 Earth Summit in Rio de Janeiro proposed the use of eco-labels to attain sustainable development, the growth and use of eco-labelling schemes have increased significantly. This study focuses on eco-labelling schemes, particularly the Singapore Green Labelling Scheme (SGLS) and the Singapore Green Building Product Certification Scheme (SGBPCS), and their contributions to the Singapore construction industry. The effectiveness of the schemes and of their drivers is determined through the analysis of survey results from two groups of samples (suppliers and architects) and interviews with some of the key stakeholders involved. It can be observed that the both the supplier and architect groups have some knowledge and awareness of eco-labelling schemes in the Singapore context. However, in terms of implementation, both schemes are only moderately effective in advocating the use and production of eco-labelled building products. It was also found that, out of several factors, “environmental rating” appears to be the only one that significantly influences the decision to use eco-labelled schemes. Furthermore, the results show that SGBPCS was not as heavily promoted in the architect group as in the supplier group. The architects perceived the SGBC advertisements to be less convincing than did the suppliers, and therefore they considered the SGBC's measures to promote the use of eco-labelled materials to be less effective. From the empirical results, strategies and measures are proposed for industry stakeholders to enhance the effectiveness of the eco-labelling schemes in the construction industry.